Chemogenetic inhibition of the ventral hippocampus but not its direct projection to the prelimbic cortex attenuates context-specific operant responding - Thomas, Callum M. P.; Bouton, Mark E.; Green, John T. (Frontiers in Behavioral Neuroscience, 2024)
Previous work has demonstrated the importance of the prelimbic cortex (PL) in contextual control of operant behavior. However, the associated neural circuitry responsible for providing contextual information to the PL is not well understood. In Pavlovian fear conditioning the ventral hippocampus (vH) and its projection to the PL have been shown to be important in supporting the effects of context on learning. The present experiments used chemogenetic inhibition of the direct vH-PL projection or the vH to determine involvement in expression of context-specific operant behavior. Rats were injected with an inhibitory DREADD (hM4Di) or mCherry-only into the vH, and subsequently trained to perform a lever press response for a food pellet in a distinct context. The DREADD ligand clozapine-n-oxide (CNO) was then delivered directly into the PL (experiment 1) and then systemically (experiment 2) prior to tests of the response in the training context as well as an equally familiar but untrained context. vH (systemic CNO) but not vH-PL (intra-PL CNO) inhibition was found to attenuate operant responding in its acquisition context. A third experiment, using the same rats, showed that chemogenetic inhibition of vH also reduced Pavlovian contextual fear. The present results suggest that multisynapatic connections between the vH and PL may be responsible for integration of contextual information with operant behavior.